Potential mobile units drive the horizontal transfer of phytoplasma effector phyllogen genes - Tokuda, Ryosuke; Iwabuchi, Nozomu; Kitazawa, Yugo; Nijo, Takamichi; Suzuki, Masato; Maejima, Kensaku; Oshima, Kenro; Namba, Shigetou; Yamaji, Yasuyuki (Frontiers in Genetics, 2023)
Phytoplasmas are obligate intracellular plant pathogenic bacteria that can induce phyllody, which is a type of abnormal floral organ development. Phytoplasmas possess phyllogens, which are effector proteins that cause phyllody in plants. Phylogenetic comparisons of phyllogen and 16S rRNA genes have suggested that phyllogen genes undergo horizontal transfer between phytoplasma species and strains. However, the mechanisms and evolutionary implications of this horizontal gene transfer are unclear. Here, we analyzed synteny in phyllogen flanking genomic regions from 17 phytoplasma strains that were related to six ‘Candidatus’ species, including three strains newly sequenced in this study. Many of the phyllogens were flanked by multicopy genes within potential mobile units (PMUs), which are putative transposable elements found in phytoplasmas. The multicopy genes exhibited two distinct patterns of synteny that correlated with the linked phyllogens. The low level of sequence identities and partial truncations found among these phyllogen flanking genes indicate that the PMU sequences are deteriorating, whereas the highly conserved sequences and functions (e.g., inducing phyllody) of the phyllogens suggest that the latter are important for phytoplasma fitness. Furthermore, although their phyllogens were similar, PMUs in strains related to ‘Ca. P. asteris’ were often located in different regions of the genome. These findings strongly indicate that PMUs drive the horizontal transfer of phyllogens among phytoplasma species and strains. These insights improve our understanding of how symptom-determinant genes have been shared among phytoplasmas.